Design a Treatment Unit to Remove Nitrates from Groundwater Using Waste of Zero Iron - Bitar, Maan; Haboub, Muhammad H.; Al-Nabghli, Nawzat (Mesopotamian Journal of Marine Sciences, 2024)
In this study, a treatment unit was designed to remove nitrate ions from groundwater using zero iron taken from waste of industrial workshops. The various conditions for the nitrate return reaction with zero iron were studied and the best conditions of batch system were determined to obtain a high removal yield, which was to conduct the treatment in an acidic medium pH =2 and add. Zero iron, with a granular size of 75µm, at a concentration of 8g/L for 120 min at normal temperature, where the removal rate reached more than 93% when using synthetic water with an initial nitrate concentration of 150ppm. The continuous treatment unit for removing nitrates in the research gave high effectiveness, as the unit includes a tank for removing nitrates with zero iron within the conditions that were deduced, followed by a tank for removing ammonium ions resulting from the first stage, then a filtration stage using a sand filter, and finally a tank for mixing the treated water with quantities determined from untreated raw water to obtain an appropriate residual level of nitrate ions. The proposed treatment unit was used in this research to treat a sample of well water containing 64 parts ppm of nitrates. The proposed treatment unit confirmed its effectiveness in treatment, as the nitrate concentration decreased to 38 ppm and was almost free of ammonium. The by-products of the treatment did not affect the Water specifications were greatly compared to the standard drinking water specifications issued by the World Health Organization